(3GdEHGfI Yf MOhO GdHdGZI hGbSGe GdfUGMIs - (3GdMSf Hf YHO Gddg Hf Sgd Hf SYjO Hf jMji Hf egQGf, CHh gdGd GdYScQj , J (B395 (3g` s
(3ChdgG (B:s
(3GdMeO ddg hdi cd fYeI EYde YdeGFc Gddg GdNjQ hPdc Ydjg Cf CMb GdYdhe Yde GdHdGZI heYQaI GdaUGMI s
(3BNQgG (B:s
(3aQZJ ef TQM GdCHhGH hGdaUhd GdJi JbOe HgG GdTQW ai Chd GdcJGH hLYdJgG hGVMI fjQI hdG eSJbje ai LejY GdLgGJ s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B196 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B560s
(3eUOQ GbJfGA GdCUd (B:s
(3GdQVhjI (B- (3eTgO s
Keywords: (3GdHdGZIs